Serum concentration of organochlorine pesticides associated with diabetes in northern Benin (West Africa) - AZANDJEME, COLETTE SYLVIE; Bouchard, Michèle; DJROLO, FRANÇOIS; HOUINATO, Dismand (My University, 2014)
Diabetes rising prevalence is of great concern in Africa because of its socio-economic impacts in a context of limited access to health care. The inappropriate use of pesticides may add to the burden of diabetes in Africa. This study was carried out in a cotton producing area of Benin in order to assess the relationship between the highest prevalence of diabetes observed in the country and organochlorine pesticide (OCP) exposure. Methods: This was a case–control study conducted in 2011. A sample of 106 subjects with diabetes and 106 non-diabetic controls were paired by age, gender, ethnicity, and residential area. Personal and socio-economic information, along with anthropometric measurements were collected. Blood samples were assayed for total lipids and 14 OCPs by gas-chromatography coupled with massspectrometry. Data were recorded for the four detectable OCPs: p,p’-dichlorodiphenyldichloroethylene (p,p’-DDE), p,p’-dichlorodiphenyltrichloroethane (p,p’-DDT), ????-hexachlorocyclohexane (????-HCH), and trans-nonachlor. Results: Serum levels of all four detected OCPs were consistently higher in diabetic subjects as compared to non-diabetic controls. The odds ratio (OR) of diabetes was nearly three-fold higher when comparing the third tertile of p,p’-DDE and p,p’-DDT and ????-HCH levels with the first tertile, without adjustment for potential confounders. The association remained significant for p,p’-DDT (OR = 2.59; 95% confidence interval (CI): 1.17-5.42) and p,p’-DDE (OR = 2.11; 95% CI: 1.01-4.54) after adjusting for a family history of diabetes, abdominal obesity, and wealth index or education. Conclusion: Our data showed that exposure to p,p’-DDT and p,p’-DDE was associated with an increased risk of diabetes. These findings have major public health implications.
Keywords: Africa; obesity; organochlorine pesticides; type 2 diabetes